Has the finance-growth link been broken? Panel data evidence from Latin America and the Caribbean - Kevin Williams (EconomiA, 2018)
This paper examines the two-way relationship between economic growth and financial development for Latin America and the Caribbean (LAC). The sample consists of 32 emerging and developing countries from LAC spanning the period 1970-2014. Controlling for country and time fixed effects, the first central finding indicates that financial development is not a significant factor driving economic growth. The evidence suggests however that larger government has a robust and significant effect on economic growth. The second key finding is that the effect of economic growth on financial development is not significantly different from zero. Together, these two main findings indicate that the finance-growth link in LAC has been broken over the 1970-2014 period. The empirical results inform economic debates in LAC and highlight the importance of public policy to improve the finance-growth relationship.
Keywords: N16; O11; G21; 330; Economic growth; Financial development; LAC